Analysis of covalent modifications of amyloidogenic proteins using two-dimensional electrophoresis: prion protein and its sialylation - Katorcha, Elizaveta (Methods Mol Biol, 2018)
A number of proteins associated with neurodegenerative disease undergo several types of post-translational modifications. They include N-linked glycosylation of the prion protein and amyloid precursor protein, phosphorylation of tau and α-synuclein. Post-translational modifications alter physical properties of proteins including their net and surface charges, affecting their processing, life-time and propensity to acquire misfolded, disease-associated states. As such, analysis of post-translational modifications is important for understanding comprehensive mechanism of pathogenesis. Recent studies documented that sialylation of the disease-associated form of the prion protein or PrP(Sc) controls the fate of prions in an organism and outcomes of prion infection. For assessing sialylation status of PrP(Sc), we developed reliable protocol that involves two-dimensional electrophoresis followed by Western blot (2D). The current chapter describes the procedure for analysis of sialylation status of PrP(Sc) from various sources including central nervous system, secondary lymphoid organs, cultured cells or PrP(Sc) produced in Protein Misfolding Cyclic Amplification.